Naidoo, Marily (Ed.), Between the real and the ideal. Ministerial formation in South African churches - Lyzette Hoffman (Acta Theologica)
From text: This book, under the editorship of Prof. Marily Naidoo, is the result of a research project on “spiritual formation and theological education” in South Africa. The co-authors write from various church denominations’ perspectives on theological training: Dutch Reformed churches, Uniting Reformed church, Anglican Church of Southern Africa, South African Presbyterian tradition, Baptist tradition, Methodist Church of Southern Africa, Lutheran tradition, Roman Catholic tradition, Charismatic context, and African Spiritual Churches.